Weight loss therapy with olanzapine orally disintegrating tablets : two case reports - Kozumplik, Oliver (Array, 2009)
The aim of this article is to report weight loss in patients with schizophrenia after switching from olanzapine standard oral tablet (SOT) to olanzapine orally disintegrating tablets (ODT). In the first case report, the patient was switched to olanzapine ODT in daily dosage of 20 mg, while in the second case report, the patient was switched to olanzapine ODT in daily dosage of 15 mg, and weight loss was similar (14 kg vs. 15 kg). Switching patients from olanzapine SOT to olanzapine ODT treatment resulted in significant weight loss that was maintained during 12 months in both case reports. Further controlled clinical investigations are necessary to evaluate change in weight during treatment with olanzapine ODT, and to improve our understanding of this change